Technical note: Evaluation of markers for estimating duodenal digesta flow and ruminal digestibility: Acid detergent fiber, sulfuric acid detergent lignin, and n-alkanes - Kozloski G.V. (2014)
The amount of digesta flowing to the duodenum is a relevant measurement for the evaluation of nutrient supply to ruminants, which is usually estimated in animals fitted with a duodenal T-type cannula using internal or external markers. This study evaluated acid detergent fiber (ADF) compared with external (C32 n-alkane) and internal [sulfuric acid lignin (ADL) and n-alkanes C31 and C33] markers for estimating duodenal flow and(or) ruminal digestibility of dry matter (DM) in cattle and sheep. In the first assay, 4 duodenally cannulated Holstein steers housed in metabolism cages, dosed with C32 n-alkane, and fed Avena strigosa plus concentrate and increasing levels of tannin extract to reduce ruminal digestibility, were used in a Latin square design. The mobile-bag technique was used to measure the intestinal disappearance of ADL and ADF from forage (Avena strigosa, Pennisetum purpureum, Cynodon dactylon, and Medicago sativa) and concentrate (corn grain, soybean meal, and sunflower meal) samples that were previously incubated in the rumen of additional fistulated steer for 12, 24, 36, or 48h. The ADF concentration in residues recovered in the feces was strongly related to the ADF concentration in residues at the duodenum (R2=0.93, standard deviation=30.0, n=901). This relationship showed a lower precision for ADL fraction (R2=0.88, standard deviation=12.6, n=590). In a second assay, duodenal flow and ruminal DM digestibility were calculated from the duodenal and fecal concentration of either marker. We observed a significant effect of marker type on ruminal DM digestibility values, and the effect of tannin treatments was observed only when ADF or ADL was used as the marker. The lowest residual error was obtained for ADF. Ruminal DM digestibility was, on average, higher for C31 and C33 n-alkanes, and the use of dosed C32 n-alkane resulted in a negative value. In the third assay, a data set of 235 individual observations was compiled from digestibility trials to compare ADF and ADL as markers for estimating duodenal digesta flow in wethers (n=204) and cattle (n=31). We observed a strong relationship between markers (R2=0.84 in sheep and R2=0.88 in cattle), but variance analysis within trials indicated that ADF was more precise than ADL. In conclusion, in digestibility trials in which fecal output was measured and spot samples of the duodenal digesta were obtained, duodenal flow and ruminal digestibility of the DM may be estimated from the relationship between the ADF concentration in feces and that in the duodenal digesta of ruminants. © 2014 American Dairy Science Association.